Innovative Media to Increase Student's Speaking Skills by Using Cake Application - Muhammd Fatwa Khusni; Agustina, Eka; Muklas, Muhamad (ENJEL: English Journal of Education and Literature, 2024)
The aim of this investigation is to assess the discernible variance between students who receive instruction prior to utilizing the Cake application as an innovative educational tool and those who are instructed subsequent to employing the Cake application in an educational context. The study adopts a quantitative research approach through an experimental design, specifically employing a pre-experimental design involving a single group of students subjected to both pre-test and post-test evaluations. This design entails assessing a solitary group without the inclusion of a control or comparative group. The data analysis entails the utilization of paired sample t-test, comparing students' pre-test and post-test scores. The results of the paired sample t-test indicate that the calculated t-value exceeds the critical t-value (19.151 > 1.684) at a significance level of α 0.05 in a one-tailed test, with degrees of freedom (df) calculated as (n-2) (33-2), resulting in 31. Consequently, the Null Hypothesis (Ho) is rejected, and the Alternative Hypothesis (Ha) is accepted. This implies that the innovative use of the Cake application demonstrates a statistically significant enhancement in students' speaking skills, particularly in the context of daily conversations.